2020
DOI: 10.1186/s13148-020-00910-9
|View full text |Cite
|
Sign up to set email alerts
|

Gene co-expression and histone modification signatures are associated with melanoma progression, epithelial-to-mesenchymal transition, and metastasis

Abstract: Background: We have previously developed a murine cellular system that models the transformation from melanocytes to metastatic melanoma cells. This model was established by cycles of anchorage impediment of melanocytes and consists of four cell lines: differentiated melanocytes (melan-a), pre-malignant melanocytes (4C), malignant (4C11−), and metastasis-prone (4C11+) melanoma cells. Here, we searched for transcriptional and epigenetic signatures associated with melanoma progression and metastasis by performin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 86 publications
0
7
0
Order By: Relevance
“…The results showed that ferroptosis inhibited the growth of malignant nasopharyngeal carcinoma cells, and the mechanism was related to DNA damage. Most of the current studies regulate cell ferroptosis progression by regulating the accumulation of lipid ROS and iron metabolism (31)(32)(33). Meanwhile, stabilizing the intracellular GSH concentration also protects cells from the lipid peroxidation reaction and subsequently suppresses the ferroptosis process (34).…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that ferroptosis inhibited the growth of malignant nasopharyngeal carcinoma cells, and the mechanism was related to DNA damage. Most of the current studies regulate cell ferroptosis progression by regulating the accumulation of lipid ROS and iron metabolism (31)(32)(33). Meanwhile, stabilizing the intracellular GSH concentration also protects cells from the lipid peroxidation reaction and subsequently suppresses the ferroptosis process (34).…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in histone “writers” or “erasers” have been associated with many pathologies, including cancer [ 31 , 45 , 67 ]. Histone modifications can be associated in CM with therapy resistance [ 68 ] and/or with epithelial–mesenchymal transition (EMT) and metastasis [ 69 ].…”
Section: Epigenetics: Another Layer Of Information In Gene Expression Regulationmentioning
confidence: 99%
“…Overexpression of G9a promotes upregulation of Notch1 signaling pathway Melanoma [27] Elevated Notch signaling associated with treatment resistance and more invasive phenotypes Melanoma [28][29][30] Notch signaling in fibroblasts creates a less favorable microenvironment Melanoma [32,33] G9a levels increase in NICD-induced model of bile duct cancer Cholangiocarcinoma [31] Metastasis H3K9me2 is increased between non-metastatic mesenchymal-like to metastatic melanoma cells Melanoma [34] HOX genes are upregulated in metastatic melanoma Melanoma [35] HOXA1 is a repressed target of G9a Glioblastoma [36] G9a represses CDH10 increasing cellular motility during hypoxia Breast Cancer [37] Autophagy G9a inhibition activates autophagy Melanoma [38] G9a represses MAP1LC3B and blocks autophagy Glioblastoma [39,40] G9a vacates autophagy related gene promoters under starvation in vitro Cervical and Pancreatic Cancer [41] G9a blocks autophagy through activation of mTOR Gastric Cancer [42] G9a has also been linked to tumor growth and metastasis. In vitro studies using serial detachment and re-adhesion of Melan-A cells also found that H3K9me2 increased between non-metastatic mesenchymal-like melanoma cells, compared to the metastatic cells [34]. The detachment and re-adhesion of cells on a plate is a highly artificial model of epithelial-to-mesenchymal transition, but additional evidence for a role of G9a in melanoma metastasis can be found in other tumor types.…”
Section: Signaling Pathway/ Cellular Mechanism Key Findings Tumor Type Referencementioning
confidence: 99%
“…G9a has also been linked to tumor growth and metastasis. In vitro studies using serial detachment and re-adhesion of Melan-A cells also found that H3K9me2 increased between non-metastatic mesenchymal-like melanoma cells, compared to the metastatic cells [ 34 ]. The detachment and re-adhesion of cells on a plate is a highly artificial model of epithelial-to-mesenchymal transition, but additional evidence for a role of G9a in melanoma metastasis can be found in other tumor types.…”
Section: The Oncogenic Roles Of G9a In Melanomamentioning
confidence: 99%